Long-term orthognathic surgical outcomes in Treacher Collins patients. Issue 3 (March 2016) - Nguyen, P.D.; Caro, M.C.; Smith, D.M.; Tompson, B.; Forrest, C.R.; Phillips, J.H.
Summary: Introduction: Treacher Collins syndrome is a rare disorder characterized by several orofacial findings including malar deficiency and hypoplastic mandibles. These patients often require a combined orthodontic–orthognathic approach to correct their malocclusion. This is most often characterized by a short posterior vertical height and an anterior open bite. Orthognathic correction often requires Le Fort I and bilateral sagittal split osteotomies. No long-term stability results have been reported after bimaxillary surgery in Treacher Collins patients. Methods: A retrospective review of all Treacher Collins patients evaluated for orthognathic surgery by a single surgeon from 1993 to 2007 was performed. Patients were divided into groups who required surgery and those who did not. Part I analyzed the cephalometric differences between the surgical (S) and nonsurgical (NS) groups. Part II of the study assessed the preorthodontic treatment ( T 1 ), preoperative ( T 2 ), immediate postoperative ( T 3 ), and 1-year postoperative ( T 4 ) cephalometric measurement variables to determine the net surgical movement ( T 3  −  T 2 ) and relapse ( T 4  −  T 3 ). Results: Twenty-two patients met the inclusion criteria, of which 11 had occlusal relationships requiring orthognathic surgery. Nine out of 11 chose to have surgery. At baseline, surgical patients exhibited a statistically significant retruded maxilla as measured by SNA and midface length compared to the NS group. In addition, the S group also had an increased gonial angle. There were significant movements in all maxillary and mandibular measurements. There was a significant relapse in the palatal plane angle when the maxilla was anteriorly impacted, with a 2.8-mm average relapse of the advancement. Relapse of the counterrotation movement of the mandible was identified, but this was not significant. Relapse did not affect the final occlusal result, which may have been compensated with postsurgical orthodontic treatment. Conclusion: Bimaxillary orthognathic surgery in the Treacher Collins patients may be performed safely with long-term dental and skeletal stability.